Effective Factors in Depression, Anxiety and Stress in the Workplace and their Impact on Job Satisfaction in Fasa Health Workers in 2019 - Touraj Khazraee; Gholamali Rayatpishe; Zeynab Heidari; Susan Janizadeh (Fasa University of Medical Sciences, 2020)
Background & Objective: Nowadays, stress and job satisfaction in the workplace are important issues in ergonomics, this is more evident in jobs such as healthcare workers that deal with human life. Therefore, the present study was designed to evaluate the level of stress, anxiety and depression and their relationship with job satisfaction of healthcare workers. Materials & Methods: This descriptive-analytical study was carried out on 196 healthcare workers of Medical Sciences University of Fasa in 2020. participants were randomly selected. The data were collected through Depression, Anxiety, Stress Questionnaire (DASS-21), Minnesota Job Satisfaction Questionnaire were analyzed by SPSS software using descriptive statistics and chi-square to determine the frequency and relationship between variables with correlation coefficient and analysis of variance. Results: In this study, it was found that about 43, 42 and 37 percent of participants suffer from various levels of depression, anxiety and stress, respectively. Also, more than 50% of participants had poor to moderate job satisfaction. The results also show that with increasing each of the variables of depression, anxiety and stress the job satisfaction score decreases. Conclusion: According to the results, it seems that decreasing stress, anxiety and job depression can increase the level of job satisfaction of employees which leads to increase in productivity and quality of work.